TECHNICS AND ITS POPULARIZATION - ZUKERSTEIN, Jaroslav (Trends in education, 2008)
The article shows possibilities of technics and technical branches popularization at Faculty of Production Technology and Management for pupils of basic schools and high schools.
Keywords: popularization; spare-time activity; school of technics; course